PENERAPAN MODIFIKASI BOLA UNTUK MENINGKATKAN HASIL BELAJAR GERAK DASAR PASSING BAWAH PERMAINAN BOLA VOLI MINI - Aldial Suryantopo; Waluyo Waluyo (PHEDHERAL, 2018)
The purpose of the study was to improve the learning results of bump pass basic motion of mini volleyball game toward the fifth grade students of SD Djamaatul Ichwan Surakarta in the academic year of 2017/2018.This research was a classroom action research (CAR). It was conducted in two cycles where each cycle consists of four stages namely as planning, action implementation, observation, and reflection. There were 29 students from the fifth grade of SD Djama’atul Ichwan as the subject of the research. The sources of the research were taken from the students, the researcher, and the teacher as a collaborator. In collecting the data, the researcher conducted tests and observation. Triangulation data was used to check the validity of the test. The data analysis used in this research was descriptive qualitative technique based on the analysis of the qualitative percantage.According to the pre-cycle result, it was found that only 9 students who were completed or only about 31.03% and there were 20 students who were not completed or about 68.97%. In the cycle I, it was obtained that the learning results of the students who were completed as many of 14 students (48,28%) and there were 15 students who were not completed (51,72%) where the affective average was (75,86%), the psychomotor was (31,03%), and the cognitive was (79,31%). In the cycle II, it was found that the learning results of students who were completed as many of 23 students or about 79.31% and there were 6 students who were not complete or about 20,69% where the affective average was (93.10%), the psychomotor was (72.41%) and the cognitive was (79.31%). According to the analysis of cycle I and cycle II, it showed the significant improvement and in accordance to the target achievements.Based on the results, it could be concluded that: modified ball in learning process could increase the learning results of bump pass basic motion in mini volleyball game toward the fifth grade students of SD Djamaatul Ichwan Surakarta in the academic year of 2017/2018.